Ecogothic Agency and the Uncanny Reimagining of Nature in The Woman in Black - Manal Shakeel (Journal of Language and Literature, 2026)
This paper proposes a novel perspective in the field of ecogothic literary criticism, wherein nature functions not as a passive backdrop but as an active agent within the Gothic. Through a closed, textual, qualitative ecogothic discourse analysis of The Woman in Black, this research draws upon Sigmund Freud’s concept of the uncanny (unheimlich), Keetley and Sivil’s notion of ecogothic spaces and the lack of ecological control, and Timothy Morton’s definition of dark ecology to contend that nature can assume the form of a supernatural force. The analysis focuses on representations of ecogothic spaces, natural phenomena, and human–nonhuman interactions to trace how ecological instability produces uncanny affect and ecophobia. By examining the familiar-turned-unfamiliar relationship between human and nonhuman entities, the findings suggest that nonhuman agency invokes uncanny affect, manifested through recurring hauntings mediated by nature. This effect is further intensified by its 19th-century English setting, where natural phenomena such as weather and the sea operate as modes of haunting, thereby inducing a fear of the nonhuman, or ecophobia, in Arthur Kipps. The study ultimately argues that, through ecophobia, the nonhuman compels both characters within the narrative and readers beyond it to confront ecological instability and human vulnerability. The paper thereby bridges literary analysis with ecological thought, suggesting that Gothic texts can cultivate environmental awareness in ways traditional ecocriticism often overlooks.